Analysis of Global Competence of Elementary School Teacher Education Students - Fadillah, Nur; Maftuh, Bunyamin; Syaodih, Ernawulan; Somantri, Mubarok (International Conference on Elementary Education, 2025)
Increasingly integrated global developments require every individual to possess global competencies, including prospective elementary school teachers who must be able to educate students to become knowledgeable, tolerant, and responsible global citizens who are able to adapt to globalization. However, various studies indicate that the global competency of university students in Indonesia is still relatively low. This study aims to describe the actual condition of global competencyamong elementary school teacher education students. This study uses a descriptive quantitative approach with elementary school teacher education students as respondents. The research instrument includes three main components of global competency: knowledge, skills, and attitudes/values, which are developed based on four dimensions of global competence. However, in this article, the focus is only on discussing the knowledge component of the global competency of elementary school teacher education students. The results of the study indicate that the knowledge component of the global competency of students still tends to be low. These findings indicate the need for learning innovation, whether in the form of developing learning models or using media and other things that can improve the knowledge component, among elementary school teacher education students in facing global challenges